Miscibility, conductivity and intermolecular interaction studies of poly(ethylene oxide) and poly(methyl methacrylate) blend based nanocomposite polymer electrolytes / Siti Rozana Abd Karim - Abd Karim, Siti Rozana (Institute of Graduate Studies, UiTM, 2018)
The addition of the third component into the polymer-salt system such as nanofiller has been extensively studied by researchers to increase the amorphous region of the polymer electrolyte system, thus improving the ion movement in the polymer chain. In most studies, the range of ionic conductivity of nanocomposite polymer electrolyte (NCPEs) can be up to ~10-4 S cm-1 and high σDC is recommended for use in applications. The success of the solid polymer electrolyte (SPEs) and NCPEs could be applied to energy storage device, electronic vehicle and capacitor for the future generation. However, the effective role of the nanofiller in promoting ion transport is not yet well understood. Therefore, this research is an effort to govern the understanding of the dispersion and effective role of the nanofiller of the most studied blend, Poly(ethylene oxide) (PEO)/Poly(methyl methacrylate) (PMMA) with lithium perchlorate (LiClO4). Differential scanning calorimetry (DSC) was used to study the thermal behaviour of the SPEs and NCPEs. A single and composition-dependent glass transition temperature (Tg) is observe for all blend compositions with increasing content of PMMA in the blend and it follow closely to that Gordon-Taylor equation. Addition of TiO2 does not give influence to the Tgs of PEO due to the absence of interaction between PEO and TiO2, but significantly raises the Tgs of PMMA. Studies on crystallinity (X*) shows that addition of PMMA and also TiO2 cause distortion on the PEO spherulites shape. The reduction of dark regions in the inter-spherulite region indicates TiO2 has weaken the linkage of O-Li through the Lewis acid-base interaction. Close inspection of the SEM micrographs observes that at low TiO2 content, the nanofiller are homogeneously disperse with no nanoparticle aggregation in the saltfree and salt-added neat PEO as well as the PEO/PMMA blend matrix. Addition of LiClO4 enhances the conductivity of PEO and it records a maximum σDC value of 1.38 × 10-6 S cm-1 at YS = 0.10, then follow by PEO/PMMA 75/25 which exhibit σDC value of 7.00 × 10-7 S cm-1 at the same amount of YS as PEO. In the presence of TiO2, the σDC values of the salt-free neat PEO and neat PMMA remain unchanged with ascending nanofiller content. However, the σDC values of the PEO/ PMMA 75/25 blend decreases by one order of magnitude. PEO/PMMA 75/25 at YS = 0.10 shows the shortest relaxation time (τmax) among the blend composition. Overall, PEO/PMMA 75/25 blend system has the best ɛ’, ɛ”, M ‘ and M “ values which are very close to the respective values of PEO system, thus accounts for its best ion conductivity among the rest of the blend systems investigated. The intermolecular interaction studies by FTIR have shown that addition of LiClO4 cause the shifting of characterized peak in PEO, PMMA and its blend, however addition of TiO2 has proved that the nanofiller is more active to the salt-added PEO/PMMA 75/25 system as compared to the parent polymers. The observation of crystal structure under XRD have shown that LiClO4 and TiO2 give effect on the crystal structure of PEO and PEO/PMMA blend, supporting the observation done by other instruments studied in this research.